2015
DOI: 10.1007/s00256-015-2220-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of gluteus medius and minimus tendon pathology and muscle atrophy in older individuals using MRI

Abstract: Gluteus medius and minimus tendon pathology and muscle atrophy increase with advancing age with progression of tendinosis to low-grade tendon tears to high-grade tendon tears. There is an associated progression in atrophy of these muscles, which may be important in fall-related hip fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 44 publications
3
49
0
2
Order By: Relevance
“…It has been reported that fatty infiltration into muscle increases with age 29,40 . Fatty infiltrate can be due to disuse in these muscles 41 , denervation of muscles 42 and as a result of certain metabolic disorders 43 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that fatty infiltration into muscle increases with age 29,40 . Fatty infiltrate can be due to disuse in these muscles 41 , denervation of muscles 42 and as a result of certain metabolic disorders 43 .…”
Section: Discussionmentioning
confidence: 98%
“…GMed and GMin atrophy has been identified in normal ageing, with atrophy present in approximately one third of people aged between 60 and 69 years and one half of the population over 70 years 29 . The progression of atrophy in advanced OA has been identified previously in unilateral OA 11 although no significant differences were identified in a meta-analysis when comparing either an OA and control group or affected and unaffected sides 9 .…”
Section: Discussionmentioning
confidence: 99%
“…6,10 There may also be a specific sequence of atrophy between the segments of the GMin, with the anterior segments seen to atrophy before the posterior segments in people with endstage OA, 11 after total hip replacement (THR) 12 and in normal aging. 13 Recent studies 14,15 have identified altered GMed muscle electromyography (EMG) in people with severe OA. However, the use of a surface electrode on GMed in these studies precludes the evaluation of individual segments of GMed and brings into question the accuracy of muscle activity recordings since EMG signal contamination from surrounding muscles is probable.…”
Section: Introductionmentioning
confidence: 99%
“…In an older individual, disorders of the GMIN tendon encompass a spectrum of tendon abnormalities ranging from chronic degenerative tendinosis to partialthickness tears and, in some cases, eventually fullthickness tears. 28 In patients with GTPS, this process typically, but not exclusively, occurs in conjunction with AB GMED pathology. Patients will often present with greater trochanteric pain that also involves the anterolateral hip region.…”
Section: Sonopathology Of the Gluteus Minimus Tendonmentioning
confidence: 99%